From Technological Utopia to a New Carrier of Civilization：Discourse Generation and Cultural Practice of Chinese-style Cultural Metaverse in the Global Context - Dongjiao, Jia (Funes. Journal of narratives and social sciences, 2026)
In the global wave of digitalization, the metaverse has shifted from a speculative concept toward a concrete arena for cultural, technological, and social experimentation. While much scholarship focuses on Western, technology-driven models, this paper examines the emerging paradigm of a Chinese-style cultural metaverse, in which digital tools are applied to preserve heritage, reframe cultural narratives, and foster international dialogue. Drawing on an interdisciplinary framework that combines cultural semiotics, the sociology of technology, and policy analysis, the study analyzes three representative case studies—the Dunhuang murals, Digital Central Axis in Beijing, and the Black Myth: Wukong game project. Through these examples, the paper argues that the Chinese cultural metaverse illustrates both opportunities and limitations in integrating cultural continuity with digital innovation. By situating these practices within global debates on the metaverse, the paper contributes a non-Western perspective to ongoing discussions about how digital environments can function not only as sites of technological experimentation but also as carriers of cultural and civilizational values.